Dampak Model Pembelajaran Problem-Based Instruction terhadap Hasil Belajar Instalasi Penerangan Listrik Siswa - Muhammad Pauzan; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The research was conducted with the aim of knowing the impact of the Problem Based Instruction learning model on the learning outcomes of Electrical Lighting Installation students of TITL Class XI SMK Negeri 5 Padang. This study uses a quasi-experimental design, namely the research using the experimental class and the control class. The subjects of this study were students of class XI TITL at SMK Negeri 5 Padang. This study uses an instrument in the form of multiple choice written test questions arranged based on the material and objectives to be achieved in learning and curriculum. the instrument requirements were tested to determine the validity and reliability of the instrument. To find out the magnitude of the impact of learning outcomes using the Problem Based Instruction model on the learning outcomes of class XI students in the Electrical Lighting Installation lesson using the effect size calculation formula. Based on the results of research and discussion that have been carried out, it shows the average value of learning outcomes from the posttest, students experience a lot of improvement. The increase was seen in the number of students who got scores exceeding the Minimum Completeness Criteria with the percentage of students who completed 92%, which was previously 77%. then the conclusion of the thesis entitled The Impact of Problem Based Instruction Learning Model on Learning Outcomes of Electrical Lighting Installation Students of Class XI Electrical Power Installation Engineering at SMK Negeri 5 Padang, a large impact in improving student learning outcomes in Electrical Power Installation subjects at SMK Negeri 5 Padang.